The Organic chemistry of drug synthesis - Lednicer, Daniel (Wiley, 2008)
The seventh volume in the definitive series that provides a quick yet thorough overview of the synthetic routes used to access specific classesof therapeutic agents, this volume covers approximately 220 new non-proprietary drug entities introduced since the publication of Volume 6.Many of these compounds represent novel structural types firstidentified by sophisticated new cell-based assays. Specifically, a significant number of new antineoplastic and antiviral agents are covered.